La política agrícola en México: evaluación a partir de una tipología de productores - Yúnez Naude, Antonio; López López, Jhair (El Colegio de México, 2021)
Abstract: The paper contains the results of a study on the production structure of basic crops in the Mexican diet and which and how many small and medium-sized farmers produce them to evaluate the orientation towards the latter in President Lopez Obrador’s food security policy design. We constructed a typology of producers of four major food crops and used it to estimate the target population of two flagship federal government programs: Guaranteed Prices (GP) and Production for Wellbeing (PW) and estimated the cost of subsidizing this population according to the guidelines of these programs. When we compared our estimates with the 2019 Budget, we found that the amount assigned to GP should have been at least 3.5 times higher, while the PW budget was 38% higher than required.